Thermomechanical coupling during large strain deformation of polycarbonate: experimental study - Song, P; Chapman, D; Graham, A; Trivedi, A; Siviour, C (Elsevier, 2024)
Polycarbonate is a widely used ductile glassy polymer that can undergo large strain deformation before failure. During the plastic deformation process, some mechanical energy is converted to heat, which, if the specimen is loaded at rates sufficient that the heat cannot conduct out of the material, can result in significant temperature rises that affect the mechanical response. Typically, this is expected to result in a reduction in stress at large strain, compared to the behaviour under isothermal conditions; however, compared to other glassy polymers, it has been observed that less softening than expected is experienced in polycarbonate at high strain rates. The current paper describes a thorough investigation of temperature rises in polycarbonate. Compression experiments are performed using a screwdriven machine, a hydraulic machine, and a long split Hopkinson bar, all instrumented with a high-speed infrared camera to measure temperature rises at strain rates between 0.01 and 2600 s-1 at a starting temperature around 20 °C. Further, temperature rises in compression experiments at 0.5 s-1 and starting temperatures between -80 to 150 °C are measured using embedded thermocouples. These span the range of the secondary- to glass-transitions of polycarbonate, allowing investigation of the effect of these transitions. These experiments are supported by finite element simulations, which use a phenomenological viscoplastic model, to ensure the thermal boundary conditions are adiabatic. Temperature rises are observed in both temperature and rate-dependent tests: experiments at higher strain rates and lower temperatures experience a greater temperature rise because of the higher yield stress; however, there are differences in the conversion ratio between plastic work and heat (Taylor Quinney coefficient), which is both temperature and rate dependent, and strongly affected by both the secondary and glass transitions.